Extraction, Purification and Immune Activity of Polysaccharide from Naxi Wuniu Tea - Ling LAI; Xiao YANG; Lin YIN; Xiaoyu CHEN; Huirong YANG; Qumin PENG; Jun LIU; Yingjie ZENG (Shipin gongye ke-ji)
Objective: The aim of this study was to isolate and purify the polysaccharide from Naxi Wuniu special morning tea, and the antioxidant and immune activities were further investigated. Methods: Firstly, the tea polysaccharides were extracted by hot water extraction method, and further purified by DEAE-52 and dextranan gel G200. Then, the basic physicochemical properties of polysaccharide were studied. And the antioxidant activities were evaluated by determined the 1,1 Diphenyl-2-trinitrobenzene hydrazine (DPPH) free radical scavenging capacity, 2,2' -diazo-di-3-ethylbenzothiazolin-6-sulfonic acid (ABTS) cationic free radical scavenging capacity, and oxygen radical absorbance capacity (ORAC). Then, the safeties of tea polysaccharide were analyzed, including endotoxin detection, RAW264.7 cells and human embryonic kidney cell 293 (HEK293) toxicity detection. Finally, the effects of tea polysaccharide on RAW264.7 cytokines (interleukin-6, IL6, tumor necrosis factor α, TNF-α, NO) release and the corresponding mRNA secretion levels, in order to obtain the immune-enhancing activity of tea polysaccharide. Results: A purified polysaccharide fraction WNp was obtained from Naxi Wuniu morning tea by using DEAE-52 anion exchange resin and Sephadex G-200. Physicochemical analysis showed that the purity of WNp was 90.26%, the protein content of WNp was 1.37%, and WNp did not contain triple helix structure. WNp was composed of glucose (Glc), galactose (Gal), arabinose (Ara), mannose (Man), rhamnose (Rha), glucuronic acid (GlcA) and galacturonic acid (GalA) at the mole ratio of 0.4:32.6:2.3:4.7:8.7:0.3:40.3, respectively. The molecular weight of WNp was 82.61 kDa. WNp showed significant scavenging abilities on DPPH and ABTS+ free radicals and a high ORAC value, that was, it had good antioxidant activities. Finally, WNp could up-regulate the mRNA expression of cytokines (IL-6, TNF-α) and NO, thereby promoting cytokine secretion (IL-6, TNF-α) and NO release, and then activate the initial immune response of RAW264.7 cells, which achieved the immuno-enhancing activity. Conclusion: The research results provide scientific basis for the deep processing and utilization of Naxi Wulu tea source.